2019
DOI: 10.1155/2019/8961409
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effects of Boron Containing Bioactive Glass on Osteogenesis and Angiogenesis of Polycaprolactone: In Vitro Study

Abstract: Polycaprolactone (PCL) has attracted great attention for bone regeneration attributed to its cost-efficiency, high toughness, and good processability. However, the relatively low elastic modulus, hydrophobic nature, and insufficient bioactivity of pure PCL limited its wider application for bone regeneration. In the present study, the effects of the addition of boron containing bioactive glass (B-BG) materials on the mechanical properties and biological performance of PCL polymer were investigated with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 58 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…The results confirm that the glass can degrade faster in dynamic conditions than in static ones. Although borate bioactive glasses have shown both mechanical and surface characteristic properties favorable for potential application in the biomedical area, most of the literature reports only results of in vivo or pre-clinical studies [ 42 , 45 , 142 , 143 , 144 , 145 ]. This is due to the fact that the area of bioactive borate glass science is still young and not sufficiently developed.…”
Section: Applications and Clinical Trialsmentioning
confidence: 99%
“…The results confirm that the glass can degrade faster in dynamic conditions than in static ones. Although borate bioactive glasses have shown both mechanical and surface characteristic properties favorable for potential application in the biomedical area, most of the literature reports only results of in vivo or pre-clinical studies [ 42 , 45 , 142 , 143 , 144 , 145 ]. This is due to the fact that the area of bioactive borate glass science is still young and not sufficiently developed.…”
Section: Applications and Clinical Trialsmentioning
confidence: 99%
“…In this study, a B-BG was obtained from boron which completely replaced sodium. Studies from previous articles have confirmed its osteoinductive aptitude and degradation characteristics (Xia et al, 2019;Deilmann et al, 2020;Houaoui et al, 2020;Li et al, 2020). Also, implants that were hard to degrade were described to cause long-term inflammatory reactions, and stress shielding occurs, which results in bone resorption and implant loosening due to mechanical properties that do not match that of the natural bone (Fedorowicz et al, 2007;Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…In particular, the VEGF overexpression was comparable with the one obtained by treating cells with particle suspensions of S53P4 BG82 and copper‐doped BG 81. When compared with composite biomaterials based on aliphatic polyesters, v‐PCL/CuChi12 performed better than PCL/boron‐containing BG16 and PLGA/collagen/ 64S BG composite films, both with and without Mg and Co doping 80. Possibly, this is, among other factors, also a consequence of the better proliferation substrate provided by electrospun fiber mats compared to a film.…”
Section: Resultsmentioning
confidence: 55%
“…At the end of the cell culture period (7 days after cell seeding), the vascular endothelial growth factor (VEGF) release from ST‐2 cells was measured. The quantification of VEGF, among several other parameters that could be monitored to characterize the angiogenic potential of copper, is generally considered the golden standard for the assessment of this property in biomaterials 16,73,80–82. In addition, ST‐2 cells are known to provide reliable results in terms of pro‐angiogenic behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation